2017
DOI: 10.3315/jdcr.2016.1237
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Bilateral Multinucleated Cell Angiohistiocytoma (MCAH)

Abstract: Background: Multinucleated Cell Angiohistiocytoma (MCAH) is a rare disease, first described by Smith and Wilson Jones in 1985. Since then, less than 100 cases have been reported in the literature. Clinically it is characterized by papules or plaques arising from a specific anatomical area such as lower extremities, dorsum of the hands and face. Some generalized cases have been reported. Main observations:We report a case of 77-year-old woman who presented with multiple itching. reddish to violaceous, flat to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…This finding suggests hormonal processes may induce pathogenetic differences between MCAH and DF. This also explains the reason why MCAH has clinical predilection for adult women (female:male ratio 3:1) . Puig et al hypothesized that mast cells, usually found adjacent to multinucleate cells, may interact with Factor XIII+ mononuclear dendritic cells and play a causative role not only in production of multinucleate cells but also in the promotion of secondary vascular hyperplasia .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding suggests hormonal processes may induce pathogenetic differences between MCAH and DF. This also explains the reason why MCAH has clinical predilection for adult women (female:male ratio 3:1) . Puig et al hypothesized that mast cells, usually found adjacent to multinucleate cells, may interact with Factor XIII+ mononuclear dendritic cells and play a causative role not only in production of multinucleate cells but also in the promotion of secondary vascular hyperplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the papules may coalesce to form larger annular lesions. [1][2][3][4][5][6] The existing literature shows most MCAHs occur in middle-to old-aged persons, affecting women more than men. In this 14-year-old boy case, the authors confirmed that MCAH can also occur in young age patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations